2011 International Electron Devices Meeting 2011
DOI: 10.1109/iedm.2011.6131681
|View full text |Cite
|
Sign up to set email alerts
|

Novel technique to engineer aluminum profile at nickel-silicide/Silicon:Carbon interface for contact resistance reduction, and integration in strained N-MOSFETs with silicon-carbon stressors

Abstract: We report a new technique of achieving reduced nickel silicide contact resistance in strained n-FETs, where a pre-silicide Aluminum (Al) implant was introduced, and the Al profile was controlled/engineered by Carbon (C). C suppresses Al diffusion during silicidation, hence retaining high concentration of Al within the NiSi. Incorporating Al within NiSi reduces the Schottky barrier height for n-Si:C contact, leading to 18 % I On improvement for Si:C S/D nFETs with no compromise on short channel effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…However, an obvious discrepancy was observed between N2 and N4 as shown in Figure 4 : a higher implantation energy of Al resulted in a higher Al concentration at the interface accompanied by a higher density of Al remaining in the NiSi film. Previous studies have indicated that Al has a dual-barrier tuning effect [ 18 , 38 ], including reducing φ bn when incorporated with nickel silicide [ 39 , 40 , 41 ] and reducing φ bp at NiSi/Si interfaces. It has been reported that the incorporation of Al in NiSi could reduce the metal work function of NiSi by up to 400 meV [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, an obvious discrepancy was observed between N2 and N4 as shown in Figure 4 : a higher implantation energy of Al resulted in a higher Al concentration at the interface accompanied by a higher density of Al remaining in the NiSi film. Previous studies have indicated that Al has a dual-barrier tuning effect [ 18 , 38 ], including reducing φ bn when incorporated with nickel silicide [ 39 , 40 , 41 ] and reducing φ bp at NiSi/Si interfaces. It has been reported that the incorporation of Al in NiSi could reduce the metal work function of NiSi by up to 400 meV [ 39 ].…”
Section: Resultsmentioning
confidence: 99%